P04.16 Tumor treating fields affect invasion properties and cell morphology of various cancer cells. (19th September 2018) - Schneiderman, R; Giladi, M; Zeevi, E; Shteingauz, A; Voloshin, T; Porat, Y; Munster, M; Kirson, E; Palti, Y
Abstract: Background: Tumor Treating Fields (TTFields) therapy is an approved modality for the treatment of glioblastoma. TTFields are delivered via continuous, noninvasive application of low intensity, intermediate frequency alternating electric fields. The antimitotic effects of TTFields have been extensively investigated. We explored other processes that may be affected by TTFields such as cellular invasion. Material and Methods: Human glioma, human and mouse melanoma, human breast cancer and human colon cancer cell lines were treated with TTFields using the inovitro system. Invasion assays were performed using a modified Matrigel coated Boyden chamber. TTFields effect on cells size, focal adhesions and stress fibers morphology was studied using immuno-fluorescent confocal microscopy. Results: Invasion was significantly reduced compared to untreated cells in all tested cell lines. Furthermore, the optimal frequency for inhibition of invasion in tested cells was 300 kHz while the optimal anti mitotic frequency leading to glioma cell death is 200 kHz. The inhibitory effect on migration was observed at electric fields intensities of 0.6 V/cm RMS which is below the 1 V/cm RMS threshold previously reported for induction of cell death. Combining TTFields with Bumetanide, an agent that inhibits cellular motility, resulted in further inhibition of glioma cell invasion. TTFields application resulted in an increase in cell size, as well as in focal adhesion size, number and peripheral distribution of the adhesion sites. Also, treated cells adopted a more flattened and spread shape in comparison with control cells. TTFields treated cells exhibit reduction in appearance of stress fibers and a dense meshwork of actin filaments around the entire cell periphery. Conclusion: Our results suggest that cancer cell motility is impaired by exposure to TTFields. The TTFields parameters (intensity and frequency) which led to the maximal inhibition of cellular motility are different from those required for exerting anti-mitotic effects. The alterations in cells morphology during exposure to TTFields may contribute to reduction in cell motility. Further studies are needed to elucidate the mechanism by which TTFields disrupts cellular motility in glioma cancer cells.